Decisions and choices about fertility and family planning: Perspectives from husbands and wives in Sudan - Dina Badri; Anja Krumeich; Bart Van de Borne (PLoS ONE, 2026)
Background The use of family planning contraceptives is an essential feature of reproductive health and rights, and safeguards women’s health. Sudan is among the countries with the lowest prevalence of family planning use in Africa. The social construction of gender norms related to preference for increased fertility and family planning decisions resides in the assumption that husbands play a limiting role in their wives’ access to family planning use. This study aims to examine to what extent husbands’ preference for increased fertility is reflected in their wives’ contraceptive use and whether and how their wives adopt their wishes in their actual family planning use. Methods This study used a qualitative approach. Khartoum and Omdurman urban cities were included in the study because they demonstrate high fertility, low contraceptive use among women, and increased unmet need. Individual interviews were conducted with forty-six participants (husbands and wives) in Khartoum and Omdurman cities. The Fertility and Reproductive Health Services Centre (FRHC) in Khartoum and Ahfad Family Health Centre (AFHC) in Omdurman were suitable for this study because of their many years of providing reproductive health services. The medical directors and key health providers assisted in identifying potential participants in the health center’s catchment areas. The participants, the husbands and their wives, were interviewed in separate spaces at FRHC, AFHC, in their homes, or at their workplace. Responses from participants were audio-recorded, transcribed, translated from Arabic to English, and thematically analyzed. Results The findings reveal that husbands’ preference for increased fertility does influence their wives’ contraceptive use. Wives who had different perceptions and were concerned about their reproductive health decided not to conform to spousal influence, seeking means to address their contraceptive needs. This is summarised as follows: *husband and wife agree about fertility and the use of family planning; *husband’s preference for increased fertility overrules wife’s considerations of contraceptive use; *some space for women to decide and use family planning methods; and *wife’s decisions to use family planning methods. Conclusion This study’s findings posit the call for partnerships forged between national health officials at the policy level, public health researchers, community workers, and community leaders to acknowledge the importance of men’s involvement in family planning. Conducting further studies and initiating awareness-raising programs focusing on men’s contraceptive literacy and, hence, attitudes towards family planning, can reduce their influence in reproductive health decisions and promote their role as supporters for women’s contraceptive use. Furthermore, national reproductive health policies must recognize the critical role health providers can play in engaging men. Implementing training initiatives for health providers to improve their roles in counseling men about the health benefits of family planning use can lead to increasing couples’ discussions about fertility-related behaviours to better safeguard their reproductive health status.